Hubungan Antara Manajemen Waktu Dan Stres Kerja Terhadap Kinerja Karyawan Pada Bank OCBC NISP Surabaya - Rheza Artanti Syahada; Larasati Ayu Sekarsari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to analyze the significance of the effect of time management on employee performance at Bank OCBC NISP Surabaya. To analyze the significance of the effect of work stress on employee performance at Bank OCBC NISP Surabaya. The method used in this research is descriptive with a quantitative approach. The results of the study are above, so it can be concluded that time management has a significant positive effect on employee performance at Bank OCBC NISP Surabaya. So, it can be said that with the help of time management employees can improve their performance, improve their study skills and get victory in their careers. Work Stress has a significant positive effect on Employee Performance at Bank OCBC NISP Surabaya. this is known from the majority of employees aged 27 years who are of productive age where the tendency of pressure received can be used as a challenge so that the stress experienced can improve performance. Keywords: Time Management, Stress, Performance